2019
DOI: 10.1042/bsr20192236
|View full text |Cite
|
Sign up to set email alerts
|

Catestatin prevents endothelial inflammation and promotes thrombus resolution in acute pulmonary embolism in mice

Abstract: Catestatin (CTS), a catecholamine-release inhibitory peptide, exerts pleiotropic cardiac protective effects. Pulmonary embolism caused by deep vein thrombosis involving vascular dysfunction. The present study aims to investigate the effects of CTS on thrombus formation that may inhibit the development of pulmonary embolism and its potential pathway. Acute pulmonary embolism (APE) model was developed as an in vivo model. The effects of CTS on mice with APE were examined. Human pulmonary artery endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…2E). These findings show that CST is both necessary and sufficient for restoring immune homeostasis in accordance with CST's role as an anti-inflammatory peptide (23)(24)(25)(26).…”
Section: Cst-ko Mice Are Hypertensive and Show Thickened Left Ventricsupporting
confidence: 56%
“…2E). These findings show that CST is both necessary and sufficient for restoring immune homeostasis in accordance with CST's role as an anti-inflammatory peptide (23)(24)(25)(26).…”
Section: Cst-ko Mice Are Hypertensive and Show Thickened Left Ventricsupporting
confidence: 56%
“…Since the physiological effects of norepinephrine and SNS mediators promote tachyphylaxis and systemic vasoconstriction it is possible that these effects contributed to detrimental vascular remodeling as evident in increased arterial stiffness parameters. Finally, although CST stand-alone generally confers protective effects on heart and vasculature, as shown in a handful of previous studies [22,23,60,61], it is possible that in the setting of IBD, a disease state characterized by persistent inflammation and increased SNS activity, effects of CST, despite being elevated in circulation, are not sufficient to compensate for adverse arterial remodeling that is propagated by the proinflammatory and adrenergic cellular pathways. However, due to a substantial evidence gap in this regard and lack of studies reporting on CST and arterial stiffness parameters, these hypothetical interactions need to be confirmed in future preclinical and mechanistic studies.…”
Section: Discussionmentioning
confidence: 97%
“…Studies implicate its connection with multiple functions throughout various systems, including vasodilatation [13], immunoregulation [14], insulin resistance [15][16][17], antimicrobial effect [18,19] and obstructive sleep apnea [20]. Furthermore, it has been reported to be a key regulator of cardiovascular function, with cardioprotective effects including exhibiting the trough suppression of atherosclerosis [21], negative inotropic and lusitropic cardiac effects [22], inhibition of coronary vasoconstriction [21], a reduction in oxidative stress in ischemic-reperfused myocardium [22], a decrease in endothelial inflammation and regulation of blood pressure [10,[23][24][25]. CST is believed to have an important role in the pathophysiology of hypertension, heart failure, reperfusion injury and coronary heart disease [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study involving an in vivo and in vitro approach investigated Cts in acute pulmonary embolism ( 99 ). Its administration in mice with this pathology increased survival as well as augmented thrombus resolution by attenuating endothelial inflammation ( 99 ).…”
Section: Cardiac Function Of Catestatinmentioning
confidence: 99%
“…In summary, based on in vitro and in vivo animal models, it was demonstrated that Cts exhibits a potential cardioprotective effect by acting directly as a cardiodepressing peptide through multiple signaling pathways ( 52 , 53 , 88 90 ), it may also reduce apoptosis of cardiomyocytes induced by oxidative stress ( 67 , 92 96 ), and is beneficial in acute pulmonary embolism ( 99 ). However, more studies are needed in these areas, in particular, regarding Cts in I/R injury of the heart ( 67 , 92 97 ).…”
Section: Cardiac Function Of Catestatinmentioning
confidence: 99%